On Control of Reaching Movements for Musculo-Skeletal Redundant Arm Model - Kenji Tahara; Suguru Arimoto; Masahiro Sekimoto; Zhi-Wei Luo (Applied Bionics and Biomechanics)
This paper focuses on a dynamic sensory-motor control mechanism of reaching movements for a musculo-skeletal redundant arm model. The formulation of a musculo-skeletal redundant arm system, which takes into account non-linear muscle properties obtained by some physiological understandings, is introduced and numerical simulations are perfomed. The non-linear properties of muscle dynamics make it possible to modulate the viscosity of the joints, and the end point of the arm converges to the desired point with a simple task-space feedback when adequate internal forces are chosen, regardless of the redundancy of the joint. Numerical simulations were performed and the effectiveness of our control scheme is discussed through these results. The results suggest that the reaching movements can be achieved using only a simple task-space feedback scheme together with the internal force effect that comes from non-linear properties of skeletal muscles without any complex mathematical computation such as an inverse dynamics or optimal trajectory derivation. In addition, the dynamic damping ellipsoid for evaluating how the internal forces can be determined is introduced. The task-space feedback is extended to the ‘virtual spring-damper hypothesis’ based on the research by Arimoto et al. (2006) to reduce the muscle output forces and heterogeneity of convergence depending on the initial state and desired position. The research suggests a new direction for studies of brain-motor control mechanism of human movements.